Intensivist -Driven Ventilator Management Shortens Duration of Mechanical Ventilation in Coronary Artery Bypass Graft Surgery Patients. (December 2022) - Dollin, Yonatan; Elliott, Brian; Markert, Ronald; Morman, Angela; Koroscil, Matthew
Background: Prolonged mechanical ventilation in post Coronary Artery Bypass Graft Surgery (CABG) is associated with deleterious effects including, increased ICU and hospital length of stay (LOS), infectious complications, and mortality. Standardized ventilator weaning protocols and the utilization of critical care physicians in post CABG patient care vary substantially among institutions. The purpose of this study was to evaluate if intensivist consultation in conjunction with a multidisciplinary, standardized ventilator weaning protocol improves outcomes in CABG patients. Materials and Methods: We performed a single-center, retrospective, before-after cohort analysis at Miami Valley Hospital in Dayton, OH, a 970-bed community hospital. Patients were divided into two arms: the before cohort or delayed-consult group (critical care consult after six hours on ventilator) and after cohort or immediate-consult group (immediate critical care consult). All patients were weaned from ventilator using a standardized weaning protocol. Results: A total of 764 patients were enrolled, 411 in the delayed-consult group and 353 in the immediate-consult group. The immediate-consult group had less time on initial mechanical ventilation than the delayed-consult group (5.86 ± 4.75 h vs. 6.00 ± 6.64 h, P = 0.038). The small advantages to immediate critical care consultation for higher percent of early extubations, fewer re-intubations, shorter ICU LOS, and lower rate of ICU readmission were not statistically significant. The two groups had similar ventilator free days, prolonged mechanical ventilation, hospital LOS, and in-hospital mortality. Conclusion: Our study suggests that intensivist-driven ventilator management in conjunction with a multidisciplinary standardized weaning protocol shortens duration of mechanical ventilation in coronary artery bypass graft surgery patients.